1987
DOI: 10.1104/pp.83.4.888
|View full text |Cite
|
Sign up to set email alerts
|

The Stoichiometry between CO2 and H+ Fluxes Involved in the Transport of Inorganic Carbon in Cyanobacteria

Abstract: The pH of the medium during CO2 uptake into the intracellular inorganic carbon (CQ) pool of a high C02-requiring mutant (Ej) and wild type of Anacystis nidulans R2 was measured. Experiments were performed under conditions where photosynthetic CO2 fixation is inhibited. There was an acidification of the medium during CO2 uptake in the light and an alkalization during CO2 efflux after darkening. A one to one stoichiometry existed between the amounts of H' appearing in the medium and CO2 taken up into the intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 14 publications
2
40
2
Order By: Relevance
“…Previous studies have suggested the participation ofa membrane-bound CA-like moiety in the transport of CO2 by Anabaena variabilis, Anacystis nidulans R2, and Synechococcus PCC 7942 (1,22,25,28). This conclusion was largely based on the observation that EZ inhibited CO2 transport (1,22,25,28) without apparent inhibition of intracellular CA (25).…”
Section: H2s Inhibition and The Mechanism Of Co2 Uptakementioning
confidence: 66%
See 3 more Smart Citations
“…Previous studies have suggested the participation ofa membrane-bound CA-like moiety in the transport of CO2 by Anabaena variabilis, Anacystis nidulans R2, and Synechococcus PCC 7942 (1,22,25,28). This conclusion was largely based on the observation that EZ inhibited CO2 transport (1,22,25,28) without apparent inhibition of intracellular CA (25).…”
Section: H2s Inhibition and The Mechanism Of Co2 Uptakementioning
confidence: 66%
“…This conclusion was largely based on the observation that EZ inhibited CO2 transport (1,22,25,28) without apparent inhibition of intracellular CA (25). Inhibition of CO2 transport by H2S in Synechococcus UTEX 625 further strengthens the view that CA and the CO2 transport system have properties in common.…”
Section: H2s Inhibition and The Mechanism Of Co2 Uptakementioning
confidence: 77%
See 2 more Smart Citations
“…The efflux of H + during calcification (Glas et al, 2012) may therefore help to constrain estimates of calcium pumping rates during calcification. Carbon dioxide uptake and proton efflux are also directly related in cyanobacteria (Ogawa and Kaplan, 1987). Ter Kuile et al (1989b) suggested that Ca 2+ is taken up by Ca 2+ -ATPase and this mechanism was subsequently used by Zeebe and Sanyal (2002) and Zeebe et al (2008) to show that H + removal is far more energy-efficient than Mg 2+ -removal during calcification.…”
Section: Ca 2+ Transport In Foraminiferamentioning
confidence: 99%